2020
DOI: 10.3934/fods.2020019
|View full text |Cite
|
Sign up to set email alerts
|

Multi-fidelity generative deep learning turbulent flows

Abstract: In computational fluid dynamics, there is an inevitable trade off between accuracy and computational cost. In this work, a novel multi-fidelity deep generative model is introduced for the surrogate modeling of high-fidelity turbulent flow fields given the solution of a computationally inexpensive but inaccurate low-fidelity solver. The resulting surrogate is able to generate physically accurate turbulent realizations at a computational cost magnitudes lower than that of a high-fidelity simulation. The deep gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In the offered case study, we demonstrated this idea on short‐term fatigue damage equivalent loads for wind turbines. Other wind‐energy related problems where CVAEs may find application are, for instance, wind farm level SCADA data modeling 48 or turbulence modeling 84,85 where finer turbulence scales are resolved in a data‐driven manner in place of the mostly empirical and mathematically simplified standard classical approaches.…”
Section: Discussionmentioning
confidence: 99%
“…In the offered case study, we demonstrated this idea on short‐term fatigue damage equivalent loads for wind turbines. Other wind‐energy related problems where CVAEs may find application are, for instance, wind farm level SCADA data modeling 48 or turbulence modeling 84,85 where finer turbulence scales are resolved in a data‐driven manner in place of the mostly empirical and mathematically simplified standard classical approaches.…”
Section: Discussionmentioning
confidence: 99%
“…This work is complementary to the work presented in a companion paper that studied enforcing statistical constraints [36]. While precise constraints have previously been used as regularization in various fields (e.g., natural language processing [37], lake temperature modeling [38,39], general dynamical systems [25], fluid flow simulations [9,11,12,40], and more specifically in turbulent flow simulations and generation [41][42][43]), the effects, performances, and best practices of imposing imprecise constraints in generative models still need further investigations.…”
Section: Scope and Contributions Of Present Workmentioning
confidence: 95%
“…A wide range of MF surrogate modelling techniques have been developed based on Gaussian processes [41][42][43] and neural networks (NNs) [44][45][46][47][48]. They have found recent applications in many areas of scientific computing, including uncertainty quantification, inference and optimization [49][50][51][52][53][54][55]. Nevertheless, MF techniques often become impractical when approximating high-dimensional systems, thereby limiting their ability to directly approximate the full solution fields of PDEs.…”
Section: Introductionmentioning
confidence: 99%